Performance analysis of Kejuruteraan Asas Jaya Sdn Bhd (KAJ) based on profitability and asset management / Nur Ezzah Kamis - Kamis, Nur Ezzah (2011)
This study is conducted to identify financial performance of Kejuruteraan Asas Jaya Sdn Bhd based on asset management and profitability. From that, the analysis of asset management and profitability performance will be carried out. From this the company can know their financial performance for their company and can make any correction and give some ideas in order to improve their performance. To analyze the data, financial statement of the company will be used to generate data. Financial statement is a secondary data for this research. To analyze the data, basic tools will be used. The profitability ratio and asset measurement ratio will be used in order to get the analysis. There are four types of common profitability ratios gross profit margin, net profit margin, return on asset and return on equity. Others are four types of common asset measurement ratio inventory turnover, account receivable, average collection period and total asset turnover. The analysis is based on five years later that compared for each year based on asset measurement and profitability measurement. This analysis is helping the company to improve their performance. From the ratio, it show that both ratios decreased regarding their profit also decreased.